2013
DOI: 10.1186/1471-2318-13-23
|View full text |Cite
|
Sign up to set email alerts
|

The minimal clinically important difference of six-minute walk in Asian older adults

Abstract: BackgroundRehabilitation interventions promote functional recovery among frail older adults and little is known about the clinical significance of physical outcome measure changes. The purpose of our study is to examine the minimal clinically important difference (MCID) for the 6-minute walk distance (6MWD) among frail Asian older adults.MethodsData from the “Evaluation of the Frails’ Fall Efficacy by Comparing Treatments” study were analyzed. Distribution-based and anchor-based methods were used to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 29 publications
4
19
1
1
Order By: Relevance
“…A distance walked of 18 to 20 m was determined to be the MCID for fragile, elderly patients undergoing rehabilitation interventions. 40,41 Our results add to the existing evidence from a systematic review of trials involving community-dwelling survivors of strokes that The 4-month assessment corresponds to 2 months after intervention in the experimental group. Data are presented as mean ± standard deviation.…”
Section: Discussionsupporting
confidence: 62%
“…A distance walked of 18 to 20 m was determined to be the MCID for fragile, elderly patients undergoing rehabilitation interventions. 40,41 Our results add to the existing evidence from a systematic review of trials involving community-dwelling survivors of strokes that The 4-month assessment corresponds to 2 months after intervention in the experimental group. Data are presented as mean ± standard deviation.…”
Section: Discussionsupporting
confidence: 62%
“…Database searches, handsearches, and consultation with an expert yielded 39 potentially relevant articles. After reviews of their titles, abstracts, and full text, 6 were found appropriate for inclusion in our review . Table summarizes the studies.…”
Section: Resultsmentioning
confidence: 99%
“…After reviews of their titles, abstracts, and full text, 6 were found appropriate for inclusion in our review. [7][8][9][10][11][12] (Table 3). comparisons with some other studies, the scale has been used previously and allows for a focus on key elements of the MCID.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations